Protocol for a randomised controlled trial of a primary care intervention to Reverse Frailty and Enhance Resilience through Exercise and dietary protein Education (REFEREE) in community-dwelling adults aged 65 and over [version 2; peer review: 2 approved] - John Travers; Roman Romero-Ortuno; Dermot Power; Peter Doran; John Langan; Fergal MacNamara; Darren McCormack; Christopher McDermott; Jude McEntire; Joanne McKiernan; Sebastian Vencken; Andrew W. Murphy; et al. (HRB Open Research, 2021)
Introduction: Resistance exercises and dietary protein have been shown to reverse frailty, yet they are not commonly offered in clinical practice. We aim to measure changes in health outcomes, including physical frailty status (SHARE-FI), clinical frailty status (CFS) and muscle mass, as a result of an optimised exercise and dietary intervention versus usual care in a primary care (PC) setting. The intervention has been derived from our systematic review and meta-analysis findings and optimised through patient and public involvement and multidisciplinary team input. Methods: This study is a multicentre randomised controlled parallel arm trial with a three month follow up. 210 eligible people aged 65 and over, no more than mildly frail, will be recruited in seven PC practices in Ireland and randomly assigned to ‘intervention’ or ‘usual care’. Intervention participants will be provided a leaflet with strength exercises, protein dietary guidance and educational discussion. Baseline measurements will include demographics, health indicators, comorbidities, malnutrition universal screening tool (MUST), frailty status (SHARE-FI, CFS) and muscle mass (bioelectrical impedance). Primary outcome will be frailty status measured by SHARE-FI at three months. Secondary outcomes include CFS, muscle mass, in-patient hospitalisation, long term care admission, and subjective ease of intervention and difference to general health. Statistical analysis will be undertaken by an independent statistician. Discussion: The diversity of tested frailty interventions and lack of clear guidance may contribute to low implementation rates. The REFEREE trial focusses on an optimised intervention for a syndrome that poses growing individual and societal challenges. It is hoped results can encourage mainstream adoption of interventions to reverse clinical frailty and build resilience in primary care. Trial registration: ClinicalTrials.gov ID NCT04628754; registered on 13 November 2020.